Pengaruh Konflik Kepentingan dan Tingkat Kesulitan Keuangan terhadap Konservatisme Akuntansi dengan Risiko Ligitasi sebagai Variabel Pemoderasi - Ardian Ardi; Kamaliah Kamaliah; Novita Indrawati (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
The aim of this study is obtain empirical evidence of the influence of conflict of interest and financial distress to accounting conservatism. This study also aims to obtain empirical evidence of litigation risk moderating the ifluence of conflict of interest and financial distress to accounting conservatism. The population of this research is the property and real estate companies listed on Indonesia Stock Exchange in 2012-2016 is 49 companies. Total samples of this research are 16 property and real estate companies used purposive sampling method. Statistical data analysis method used is linear regression analysis and Moderated Regression Analysis (MRA). The analysis results found that the conflict of interest has no effect on accounting conservatism, financial distress has a effect on accounting conservatism, litigation risk is reinforce the effect of conflict of interest to accounting conservatism, and litigation risk is not able to moderate the effect of financial distress to accounting conservatism.